Grain‐Boundary and Thermally Stimulated Current Characteristics of Y2O3‐Doped ZnO Varistor. Issue 11 (19th August 2013) - Tu, Youping; Zheng, Zenghui; Li, Xiao; Wang, Qian; Luo, Meixin
Abstract : The doping of rare‐earth oxides can greatly improve the electrical characteristics of ZnO varistors. Thermally stimulated current (TSC) characteristic test, capacitance voltage ( C–V ) characteristic test, scanning electron microscope (SEM) test, and voltage current ( V–I ) test were carried out to study the influence of Y2 O3 content on the electrical properties of ZnO varistors in this study. The results show that the grain size decreases while the voltage gradient increases as the Y2 O3 content is increased. The reaction of Y2 O3 with other additives leads to the decrease in grain‐boundary defects, which accounts for the decrement of barrier height, donor density, and surface state density. The trap level and trapped charge of ZnO varistors decrease as the Y2 O3 content is increased from 0.3 to 0.9 mol%, which means the shallow traps inside ZnO varistors reduce, and the Y2 O3 additive can greatly improve the TSC characteristic of ZnO varistors.